Sacrificial youth - Losurdo, Joe; Porter, Sam (Actor); Bakker, Robert P.; O'Connell, (Actor); Regressive Films; Leomark Studios (Firm) ([Chicago, Ill.] : Regressive Films, 2013)
Sacrificial youth is a hardcore punk musical that tells the story of TJ, a teenager caught at the crossroads of good and evil. When a multi-national corporation hatches an evil plot of biblical proportions to destroy the scene, TJ is forced to accept his fate as the chosen one to stand up and fight back.
Contains strong language including swear words.
Originally released as a motion picture in 2013
Sam Porter, Rob Bakker, Mike O'Connell, Kate Lane, Larry Gutkin, John Kopanski, Christina Tillman, Dante Reyes, Venus Zarris.
Cinematographer, Wes Tabayoyong ; editor, Joe Losurdo.
In English; with optional English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed February 2, 2018)
Keywords: Corporations -- Drama; Conspiracies -- Drama; Good and evil -- Drama; Musical films; Punk films; Feature films; Internet videos; Streaming video